Implementation of the Social Assistance Program for Handling Uninhabitable Houses - Rachel Zefanya Caesario; Gisheyla Salma fithriya; Nazwa Muthia; Elsya Dwi Damayanti; Minati Fitriana Harahap (Administratie: Jurnal Administrasi Publik, 2025)
This research is of high urgency in the context of handling housing problems for the low-income community (LIC) in Serang Regency, primarily through the Social Assistance Program for Handling Uninhabitable Houses (BSP-RTLH). The main objective of this research is to evaluate the implementation of the BSP-RTLH program and its impact on improving the quality of life of the community. The method used is descriptive qualitative, with data collection through in-depth interviews with key informants, namely the Head of the Housing Division of the Public Housing and Settlement Area Agency of Serang Regency, the Head of Sindangheula Village, and the Social Welfare Staff of Mekar Baru Village. The results show that the implementation of the BSP-RTLH program in Serang Regency is still facing various obstacles. Although there are six evaluation indicators referenced from Van Meter and Van Horn's theory, program implementation has not been fully effective. The main obstacle lies in the lack of understanding of program implementers and low community participation in the process. In addition, the socialization of the program has not been optimal, so many people do not understand the purpose and benefits of this assistance. Based on these findings, it is recommended that compliance with SOP and juknis be maintained and evaluated regularly to ensure program relevance. Capacity building of human resources through socialization and intensive training should be intensified, and the role of local facilitators should be strengthened as agents of community education and assistance. Coordination between the Housing and Settlement Office and kelurahan officials should be strengthened with technical training to ensure adequate verification and assistance. The positive attitude of implementers needs to be maintained through appreciation and regular evaluation forums to increase commitment. Inter-organizational communication should be strengthened with regular meetings and the use of technology, as well as the expansion of cooperation networks with stakeholders. From the environmental aspect, socialization in the community should be improved, disciplinary enforcement of proposal submission procedures should be strengthened, and criteria for beneficiaries should be carried out transparently so that the program can have an optimal socio-economic impact.